Importance given to the reasons for sport participa- tion and to the characteristics of a fitness service - Damásio, António; Campos, Francisco; Gomes, Ricardo (Arena-Journal of Physical Activities, 2017)
The main motives for sports participation in Portugal are: health improve- ment (67%), relaxation (32%) and better physical appearance (28%) (Euro- pean Commission, 2014). Regarding fitness activities, gym location (close to home or workplace), price and flexible schedules are the main characteristics when deciding the place for sports practice (Cracknelll, 2015). The present study has two aims: to analyse the importance given by the clients to the reasons for fitness participation and to assess the importance given to the characteristics of a fitness service. Forty-five fitness clients, which were also university students, participated in this study. Regarding the first objective, health related motives [adopt a healthy lifestyle (M=6.18) and improve health (M=6.09)] were the most important. Regarding the second objective, facil- ity hygiene and cleanliness (M=6.33) price (M=6.27) good technical sup- port (M=6.20) and a diversified schedule (M=6.16) are the factors to which most importance is given. This research supports Franco, Pereira and SimÃµes (2008) and Campos (2015) statements, arguing that, gym and health club owners should consider the importance given by the clients to the facilitiesâ€™ characteristics and their motivations for sports participation. Â